Bibliometric research on analysis of links between periodontitis and cardiovascular diseases - Tang, Kuangyun; Wu, Yongjia; Zheng, Qianhan; Chen, Xuepeng (Frontiers in Cardiovascular Medicine, 2023)
Background Periodontitis (PD) and cardiovascular diseases (CVD) rank among the most prevalent pathologies worldwide, and their correlation has been a subject of prolonged investigation. Numerous studies suggest shared etiological factors; however, a definitive causal connection remains unestablished. The objective of this study was to employ bibliometric and visual analyses in order to comprehensively examine the overarching characteristics, focal areas of research, and prospective trends pertaining to the PD-CVD relationship. Methods We sourced articles, reviews, and online publications on PD- and CVD- research from the Web of Science Core Collection (WoSCC) spanning from January 1, 1993, to May 15, 2023. A triad of analytical tools (R-Bibliometrix, VOSviewer 1.6.19, and CiteSpace 6.2.R3) were utilized to facilitate collaboration network analysis, co-citation analysis, co-occurrence analysis, and citation burst detection. Results Out of the 1,116 publications that fulfilled the eligibility criteria in the WoSCC database, the comprehensive characteristics analysis divulged a sustained growth trend in publication frequency. In the cluster analysis of reference co-citation and keyword co-occurrence, prominent themes such as “periodontitis”, “cardiovascular diseases”, “inflammation”, “Porphyromonas gingivalis”, and “atherosclerosis” consistently emerged. Contemporary topics such as “peri-implantitis,” “COVID-19”, “cardiovascular risk factors,” and “endocarditis” were pinpointed as burgeoning research hotspots. Conclusion Based on this bibliometric study, in the field of association studies between PD and CVD, the etiologic mechanisms of both diseases have been intensively studied in the last three decades. Periodontal pathogens might serve as potential initiating factors linking PD and CVD. Inflammation may constitute a significant etiological factor shared by both diseases. Several emerging topics, such as COVID-19 and peri-implantitis, exhibit promising potential. This exhaustive overview casts light on pivotal research arenas, augmenting the field's understanding and stimulating further scholarly investigations.